What predicts health facility delivery among women? analysis from the 2021 Madagascar Demographic and Health Survey - Ebenezer Kwesi Armah-Ansah; Eugene Budu; Elvis Ato Wilson; Kenneth Fosu Oteng; Nhyira Owusuaa Gyawu; Bright Opoku Ahinkorah; Edward Kwabena Ameyaw (BMC, 2024)
Abstract Background One of the pivotal determinants of maternal and neonatal health outcomes hinges on the choice of place of delivery. However, the decision to give birth within the confines of a health facility is shaped by a complex interplay of sociodemographic, economic, cultural, and healthcare system-related factors. This study examined the predictors of health facility delivery among women in Madagascar. Methods We used data from the 2021 Madagascar Demographic and Health Survey. A total of 9,315 women who had a health facility delivery or delivered elsewhere for the most recent live birth preceding the survey were considered in this analysis. Descriptive analysis, and multilevel regression were carried out to determine the prevalence and factors associated with health facility delivery. The results were presented as frequencies, percentages, crude odds ratios and adjusted odds ratios (aORs) with corresponding 95% confidence intervals (CIs), and a p-value < 0.05 was used to declare statistical significance. Results The prevalence of health facility delivery was 41.2% [95% CI: 38.9-43.5%]. In the multilevel analysis, women aged 45-49 [aOR = 2.14, 95% CI = 1.34-3.43], those with secondary/higher education [aOR = 1.62, 95% CI = 1.30-2.01], widowed [aOR = 2.25, 95% CI = 1.43-3.58], and those exposed to mass media [aOR = 1.18, 95% CI = 1.00-1.39] had higher odds of delivering in health facilities compared to those aged 15-49, those with no formal education, women who had never been in union and not exposed to mass media respectively. Women with at least an antenatal care visit [aOR = 6.95, 95% CI = 4.95-9.77], those in the richest wealth index [aOR = 2.74, 95% CI = 1.99-3.77], and women who considered distance to health facility as not a big problem [aOR = 1.28, 95% CI = 1.09-1.50] were more likely to deliver in health facilities compared to those who had no antenatal care visit. Women who lived in communities with high literacy levels [aOR = 1.54, 95% CI = 1.15-2.08], and women who lived in communities with high socioeconomic status [aOR = 1.72, 95% CI = 1.28-2.31] had increased odds of health facility delivery compared to those with low literacy levels and in communities with low socioeconomic status respectively. Conclusion The prevalence of health facility delivery among women in Madagascar is low in this study. The findings of this study call on stakeholders and the government to strengthen the healthcare system of Madagascar using the framework for universal health coverage. There is also the need to implement programmes and interventions geared towards increasing health facility delivery among adolescent girls and young women, women with no formal education, and those not exposed to media. Also, consideration should be made to provide free maternal health care and a health insurance scheme that can be accessed by women in the poorest wealth index. Health facilities should be provided at places where women have challenges with distance to other health facilities. Education on the importance of antenatal care visits should also be encouraged, especially among women with low literacy levels and in communities with low socioeconomic status.